Perlindungan Hukum Terhadap Masyarakat Di Wilayah Pertambangan Dalam Penyelesaian Sengketa Pengelolaan Lingkungan Hidup - Simbala, Yumi; Djefry Welly Lumintang; Vecky Gosal (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Mining activities that are increasingly uncontrolled have various impacts on the community and life around the mine, including; Environmental damage, high levels of pollution (soil, water and air), also cause disruption to the wider community in the form of damage to houses and public facilities. This research aims to determine the form of legal protection for communities in mining areas who suffer losses related to mining activities, as well as to determine dispute resolution in the form of demands for compensation from communities around mining locations. The research method uses normative research methods with a statutory approach, conceptual approach and case approach. Apart from that, empirical research is also used to see the reality that occurs in the field. The results of the research show that the legal implications regarding the protection of communities in mining areas in environmental management are problematic in their resolution due to the government’s indifference and also regarding the compensation provided by mining business actors. The responsibility for restoring mining land is the responsibility of business actors as an obligation to restore the social and economic environment as a result of the impact of mining activities on communities in mining areas.